2020
DOI: 10.1002/adom.202000669
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Electrodes for Flexible Organic Solar Cells with Efficiencies over 16%

Abstract: Flexible organic solar cells (OSCs) are very promising for use in portable power supply devices due to the advantages of low‐cost, light‐weight, and flexibility. However, the efficiencies of flexible OSCs are limited by the flexible transparent electrodes owing to their nonoptimal electrical, optical, and mechanical properties. To address these challenges, leaf‐like biomimetic electrodes are proposed to achieve an efficient light capture and glossy surface for a high‐efficiency flexible OSC. To mimic the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…[16] A recent study demonstrated that a flexible OPV with an outstanding PCE of 16.1%, based on a leaf-like biomimetic design with efficient light capture and glossy surface, retained ≈75% of its initial efficiency for storage at 60 h in air. [7] Recently, ultrathin OPVs with a total thickness of less than 10 μm have been developed to provide extreme mechanical compliance and deformability, [17,18] which is beneficial for integration with conformable wearable sensors or electronic skin (eskin). [2,[19][20][21][22] For example, an ultrathin OPV with a total thickness of 3 μm can be integrated with organic electrochemical transistors (OECTs) to realize self-powered cardiac signal detection.…”
Section: Introductionmentioning
confidence: 99%
“…[16] A recent study demonstrated that a flexible OPV with an outstanding PCE of 16.1%, based on a leaf-like biomimetic design with efficient light capture and glossy surface, retained ≈75% of its initial efficiency for storage at 60 h in air. [7] Recently, ultrathin OPVs with a total thickness of less than 10 μm have been developed to provide extreme mechanical compliance and deformability, [17,18] which is beneficial for integration with conformable wearable sensors or electronic skin (eskin). [2,[19][20][21][22] For example, an ultrathin OPV with a total thickness of 3 μm can be integrated with organic electrochemical transistors (OECTs) to realize self-powered cardiac signal detection.…”
Section: Introductionmentioning
confidence: 99%
“…Tang and coworkers reported a biomimetic FTE, which is composed of ZnO protecting layer, conductive AgNWs, light‐scattering polystyrene spheres, and PI substrate. [ 62 ] The biomimetic FTE offers high transmittance (88.2%), low resistance (23.4 Ω sq −1 ), and small surface roughness (2.4 nm). The inverted flexible OSCs with PM6:N3:PC 71 BM blend achieved a PCE of 16.1%, and kept 13.7% after 5000 cycles bending with a small radius (1.0 mm).…”
Section: Flexible Oscs Based On Agnwsmentioning
confidence: 99%
“…[ 49 ] Consequently, with the continuous development of efficient photoactive materials, significant progress has been achieved for flexible OSCs in recent years. [ 21,26–28,50–64 ] As shown in Table 1 , the photovoltaic performances of representative flexible OSCs are summarized, and the molecular structures of corresponding materials are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Flexible organic solar cells (OSCs) have become a popular research field, owing to the advantages of low cost, light weight, ease of fabrication, wearability, portability, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Transparent electrode fabrication is regarded as one of cores that determine the power conversion efficiency (PCE) and the device fabrication cost [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several emerging transparent conducting materials show a promise as ITO alternatives and have the potential for large-area coverage and some degrees of mechanical flexibility. These materials include transparent conducting polymers [22][23][24][25][26][27], carbon nanotubes [28], graphene [14,29], and metallic nanowires [2,5,6]. Among them, the solution-processed conducting polymeric films of poly (3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) were under intense investigation.…”
Section: Introductionmentioning
confidence: 99%